2013
DOI: 10.1371/journal.pone.0063212
|View full text |Cite
|
Sign up to set email alerts
|

Progressive White Matter Microstructure Damage in Male Chronic Heroin Dependent Individuals: A DTI and TBSS Study

Abstract: BackgroundTo investigate the WM microstructure deficits in heroin dependent individuals (HDIs) with different length of heroin dependence, and to investigate whether these WM deficits can be related to the duration of heroin use and to decision-making deficits in HDIs.Methodology/Principal FindingsThirty-six HDIs [including eighteen sHDIs (duration of heroin dependent is less than 10 years) and eighteen lHDIs (duration of dependent is between 10∼20 years)] and sixteen healthy controls participated in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 38 publications
5
62
0
Order By: Relevance
“…Nevertheless, it is noteworthy that the pattern of differential diffusivities (more prominent increases in RD) has been frequently observed in clinical samples including substance use (Qiu et al, 2013;Willi et al, 2016), HIV infection (Leite et al, 2013), and related comorbid conditions (Tang et al, 2015). Collectively, this pattern is thought to be characteristic of chronic white matter degeneration (Burzynska et al, 2010).…”
Section: Tract-based Spatial Statistics -Whole Brain Approachmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, it is noteworthy that the pattern of differential diffusivities (more prominent increases in RD) has been frequently observed in clinical samples including substance use (Qiu et al, 2013;Willi et al, 2016), HIV infection (Leite et al, 2013), and related comorbid conditions (Tang et al, 2015). Collectively, this pattern is thought to be characteristic of chronic white matter degeneration (Burzynska et al, 2010).…”
Section: Tract-based Spatial Statistics -Whole Brain Approachmentioning
confidence: 97%
“…For example, in schizophrenia patients, FA correlates with measures of verbal memory, attention, and executive functions in tracts specifically known to mediate these respective functions (Lim et al, 2006). Likewise, lower FA and higher diffusivity in frontal and parietal tracts has been linked with poorer performance on an affective decision-making task in cocaine-dependent (Lane et al, 2010) and heroin-dependent subjects (Qiu et al, 2013). On the other hand, when age and motor function were controlled for in cognitively normal adults, associations were identified between executive functioning, memory, and information processing, and white matter tract integrity in the corresponding functional regions (Sasson, Doniger, Pasternak, Tarrasch, & Assaf, 2012).…”
Section: Tract-based Spatial Statistics -Whole Brain Approachmentioning
confidence: 99%
“…These studies find diminished white matter integrity in frontal, temporal, and parietal regions (Bora et al, 2012; Liu et al, 2008; Qiu et al, 2013), as well as specific tracts connecting neuronal regions (Upadhyay et al, 2010). Associations between duration of use and FA in these white matter regions have been observed such that the longer the duration of opioid abuse the more damage to the tissue.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 95%
“…Additionally, examination of white matter tracts has implicated a number of pathways where decreased FA in opiate abusers have been observed including the stria terminalis, ventral amygdalofugal fibers, and uncinuate fasciculus that connect the amygdala with other subcortical and cortical structures, including the nucleus accumbens and insula (Upadhyay et al, 2010). Some researchers have explained these white matter changes as damage to only myelin (Bora et al, 2012), whereas others have found evidence for both myelin pathology and axonal injury (Qiu et al, 2013), possibly due to opioid-induced leukoencephaly (Liu et al, 2008). There is also evidence for increased ischemic lesions in heroin abusers (Andersen and Skullerud, 1999), which may result from perfusion deficits and/or ischemia related to respiratory suppression, overdoses, disturbance of consciousness, vasculitis, and rhabdomyolosis in heroin abusers (Qiu et al, 2013).…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
See 1 more Smart Citation